GOVERNANCE OF OXYGEN TOURISM DEVELOPMENT BASED ON COMMUNITY-BASED TOURISM (CBT) IN GILI IYANG, SUMENEP REGENCY - Imam Hidayat; Anis Kurli; Rillia Aisyah Haris; Deny Feri Suharyanto; Rindy Antika Sugandha (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2026)
One of the top 5 tourist destinations with the highest oxygen levels in the world is in Indonesia, namely on Gili Iyang Island, Sumenep Regency, East Java. It is a nature tourism spot with high oxygen levels ranging from 20.9% to 21.5% and features the richness of local culture, adding to its appeal for visitors. However, these superior resources have not been managed well; there is no participation from the local community in developing the tourism industry, the uniqueness of local traditions, cuisine, and culture is not maximized. There is weak government support for tourism infrastructure, and there is no empowerment or development of the local community to support the tourism industry. Research objective: To develop a governance framework for tourism development based on community-based tourism (CBT) as a recommendation for reformulating the stages of sustainable tourism development, taking into account local wisdom as the main asset in enhancing the quality of the tourism industry on Oxygen Island, Gili Iyang. Research method: This study uses a descriptive qualitative method with an observational study, involving the observation of tourist behavior and interactions, tourism policies in Sumenep, the behavior of tourism-aware groups, and other stakeholders involved in tourism development.